Clinical features of a new disease concept, IgG4-related thyroiditis. (August 2013) - Watanabe, T; Maruyama, M; Ito, T; Fujinaga, Y; Ozaki, Y; Maruyama, M; Kodama, R; Muraki, T; Hamano, H; Arakura, N; Kadoya, M; Suzuki, S; et al.
<x xml:space="preserve">Abstract</x> Objectives: Immunoglobulin (Ig)G4-related disease is a recently proposed systemic disorder that includes autoimmune pancreatitis (AIP), Mikulicz's disease, and various other organ lesions. In the present retrospective study, we examined whether thyroid lesions should also be included in IgG4-related disease (Ig4-RD) under the new term IgG4-related thyroiditis. Method: We enrolled 114 patients with Ig4-RD, including 92 patients with AIP, 15 patients with Mikulicz's disease, and seven patients with IgG4-related cholangitis, and analysed clinical findings, function, serum values of activity markers, computed tomography (CT) images, and histology of the thyroid gland. Results: Among the 22 patients (19%) in our cohort who were found to have hypothyroidism [thyroid stimulating hormone (TSH) > 4 mIU/L], 11 patients had clinical hypothyroidism [free thyroxine (FT4) < 1 ng/dL] and 11 patients had subclinical hypothyroidism (FT4 ≥ 1 ng/dL). Serum concentrations of IgG, IgG4, circulating immune complex (CIC), and β2-microglobulin (β2-MG) were significantly higher in the hypothyroidism group compared with the remaining 92 euthyroid patients, and serum C3 concentration was significantly lower. After prednisolone treatment, TSH values had decreased significantly (p = 0.005) in this group and FT4 values had increased significantly (p = 0.047). CT images showed that the thyroid glands of patients with clinical hypothyroidism had a significantly greater volume than those of the euthyroid and other groups. Pathological analysis of one resected thyroid gland disclosed a focused lesion with infiltration of lymphocytes and IgG4-bearing plasma cells and loss of thyroid follicles. Conclusions: Thyroid lesions associated with hypothyroidism can be considered as a new disease termed IgG4-related thyroiditis. Awareness of this condition should lead to appropriate corticosteroid treatment that may prevent progression to a fibrous state.